Liberating Hidden Voices: A Feminist Action Research Study to Empower Homeless Women. Issue 2 (2nd July 2020) - Speedlin, Stacy; Haberstroh, Shane; McVay, Katherine; Elliott, Jordan; Anderson, Aneesa
ABSTRACT: Within the homeless population in the United States, women are over-represented among homeless families and are under-represented in society and in homeless studies. This feminist action research study examined the experiences of homeless women and their service needs. Overall, findings revealed the complexities of unsheltered life for women and highlighted the challenges of living in an unsheltered homeless setting and accessing services. The participant's stories emphasized the importance of social justice training for future counselors.